Digital Transformation and Sustainability in Islamic Finance: Evidence from Geopolitical Uncertainty in an Emerging Regional Economy - Rauzatul Jannah; Harjoni Desky; Iskandar Iskandar (Universitas Islam Negeri Ar-Raniry, 2026)
Amid rapid digital advancement, empirical evidence linking digital transformation with sustainability principles in Islamic economics and finance remains limited. The evolution of this sector has increasingly reflected improvements in operational efficiency, expanded financial inclusion, and the emergence of technology-driven innovations. This study evaluates the effects of digital transformation, sustainable growth, and geopolitical uncertainty on the performance of Islamic economics and finance, with a focus on Islamic financial institutions in Lhokseumawe City. A quantitative approach is employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), based on data collected from 279 users of Islamic financial services. The findings reveal that digital transformation, sustainable growth, and geopolitical factors each exert a positive and significant influence on the performance of Islamic economics and finance. In addition, digital transformation functions as a mediating mechanism that links sustainable growth to financial performance, indicating its role in translating sustainability-oriented initiatives into measurable outcomes. These results highlight the importance of strengthening the integration between digital innovation and sustainability agendas, while also addressing external pressures arising from geopolitical uncertainty and global technological change. The study offers insights for advancing theoretical integration across these domains and provides direction for enhancing institutional adaptability, inclusiveness, and resilience within Islamic financial systems. Transformasi Digital dan Keberlanjutan dalam Keuangan Islam: Bukti dari Ketidakpastian Geopolitik di Ekonomi Regional Berkembang. Meski teknologi digital berkembang sangat pesat, studi empiris tentang hubungan antara transformasi digital dan prinsip keberlanjutan dalam ekonomi dan keuangan Islam masih terbatas. Transformasi digital telah mempengaruhi dinamika ekonomi dan keuangan Islam lewat peningkatan efisiensi operasional, perluasan inklusi keuangan, serta inovasi berbasis teknologi. Penelitian ini bertujuan menilai pengaruh transformasi digital, pertumbuhan berkelanjutan, dan ketidakpastian geopolitik terhadap kinerja ekonomi dan keuangan Islam, khususnya pada lembaga keuangan Islam di Kota Lhokseumawe. Penelitian ini menggunakan pendekatan kuantitatif dengan metode Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data diperoleh dari 279 responden yang merupakan pengguna layanan keuangan Islam di Kota Lhokseumawe. Hasil studi menunjukkan bahwa transformasi digital, pertumbuhan berkelanjutan, dan faktor geopolitik memiliki pengaruh positif dan signifikan terhadap penguatan ekonomi dan keuangan Islam. Selain itu, transformasi digital berfungsi sebagai variabel mediasi yang menghubungkan pertumbuhan berkelanjutan dan kinerja keuangan Islam. Temuan ini menegaskan pentingnya pemanfaatan teknologi digital secara efektif sebagai mekanisme kunci dalam mendukung keberhasilan pertumbuhan berkelanjutan di sektor keuangan Islam. Studi ini memberikan kontribusi dalam pengembangan kerangka teoretis yang lebih terpadu serta menawarkan arah bagi peningkatan adaptabilitas, inklusivitas, dan ketahanan lembaga keuangan Islam.